Aviso a los navegantes : la traducción al español de Economía y sociedad de Max Weber - Morcillo Laiz, Álvaro (El Colegio de México, 2012)
Any scholarly reading of Max Weber’s Economía y sociedad may substantially benefi t from a comparison between the German and the Spanish version of the work. This article fulfi lls this task. In order to accomplish it, the following aspects are examined: the external outlook of Economía y sociedad, its shortcomings in terms of oversights, changes in the word sequence, omissions, biased translations of a concept, and the rendering of Weber’s terms of the art, like Verband organization, Ordnung order y Betrieb establishment. In Economía y sociedad these terms are sometimes translated in ways that suggets connotations absent from the German original, suppress others that were actually implicit, without the required consistency. These shortcomings set hurdles to a proper understanding of the work and speak for a new translation.